2005
DOI: 10.1108/00907320510597408
|View full text |Cite
|
Sign up to set email alerts
|

Incoming international students and the library: a survey

Abstract: This study was undertaken to assess incoming international students' exposure to libraries, computer literacy skills, and to determine their library needs. Results from a survey conducted in August 2003 include demographic information about incoming students, computer and library use before coming to the United States, library concepts that are new to them, and opinions about the library. Survey results show that international students arrive in the U.S. with high levels of computer literacy and that most inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…Guides to practice suggest strategies for libraries to support international students, including cultural awareness training for staff, targeted instruction and help, and translated information guides and multi-language collections (Peters, 2010;Ye, 2009 (Jackson, 2005), the importance of explaining and promoting services is often highlighted (Knight et al, 2010;Liu & Winn, 2009;Sharman, 2017). However, there is limited research to guide how and why this can be realised, or that considers international students' library experience or information literacy learning.…”
Section: Hughes Hall and Pozzi Library Experience And Information Litmentioning
confidence: 99%
See 2 more Smart Citations
“…Guides to practice suggest strategies for libraries to support international students, including cultural awareness training for staff, targeted instruction and help, and translated information guides and multi-language collections (Peters, 2010;Ye, 2009 (Jackson, 2005), the importance of explaining and promoting services is often highlighted (Knight et al, 2010;Liu & Winn, 2009;Sharman, 2017). However, there is limited research to guide how and why this can be realised, or that considers international students' library experience or information literacy learning.…”
Section: Hughes Hall and Pozzi Library Experience And Information Litmentioning
confidence: 99%
“…The library also offers them a safe, central social gathering spot (Liao, Finn, & Lu, 2007). Despite frequent use of the library and high attendance at library orientations (Liu & Winn, 2009;Shao & Scherlen, 2011), international students are often unaware of the full range of services available, particularly research assistance and online chat (Jackson, 2005;Knight et al, 2010;Shaffer, Vardaman, & Miller, 2010;Sharman, 2017).…”
Section: Hughes Hall and Pozzi Library Experience And Information Litmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moving from theory to practice, further studies in the library literature offer practical suggestions as to how to take this knowledge of language learning and put it to good use when working with international students. Some of these ways include: offering library instruction sessions for international students that incorporate language acquisition concerns along with the development of library skills, 7 enabling librarians to work on a more meaningful level with this group of students, 8 learning more about international students' initial level of library knowledge before designing programs, 9 and considering language needs of international students in one-onone transactions as well as in classroom settings.…”
Section: May 2010mentioning
confidence: 99%
“…International Students and Challenges to Academic Library Use Much research on the challenges faced by international students in utilizing Western academic libraries has been carried out over the past 30 years (Amsberry, 2008;Baron & Strout-Dapaz, 2001;Jackson, 2004;Mu, 2008;SarkodieMensah, 1998). Hughes (2010) suggested that there are three overarching themes that define the challenges faced by international students in terms of effectively using academic libraries, which are "environmental, culturallinguistic, and affective" (p. 3).…”
Section: Downloaded By [Nazarbayev University Library] At 21:31 25 Jamentioning
confidence: 99%